2018
DOI: 10.3329/bpj.v21i2.37921
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia (Bitter melon) in Combination with Metformin Potentiates Hypoglycemic and Hypolipidemic Effects in Alloxan-induced Diabetic Rats

Abstract: The present study was designed to investigate the effects of bitter melon (Momordica charantia) in combination with a standard oral hypoglycemic agent metformin on alloxan induced diabetic rats (AIDRs). Both the plant extract and the drug, individually and in combination, were subjected in vivo for two weeks (short term) and four weeks (long term) treatment protocol to determine blood glucose level, lipid profile and liver glycogen level using Swiss Albino rats. In short term treatment protocol, bitter melon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…The major constituent of bitter gourd is charantin, which improves insulin sensitivity by increasing glucose uptake via glucose transporter-4 in skeletal muscle cells, resulting in cellular uptake and utilization of glucose [ 42 ]. This mechanistic finding was in line with an in vivo study where feeding mice with metformin (15 mg/kg) in combination with bitter gourd (300 mg/kg) showed synergistic hypoglycemic properties when compared to those that were fed with metformin or bitter ground alone [ 43 ]. However, the use of herbal medicine and higher doses of metformin was not found to be associated with good glycemic control in this study.…”
Section: Discussionsupporting
confidence: 83%
“…The major constituent of bitter gourd is charantin, which improves insulin sensitivity by increasing glucose uptake via glucose transporter-4 in skeletal muscle cells, resulting in cellular uptake and utilization of glucose [ 42 ]. This mechanistic finding was in line with an in vivo study where feeding mice with metformin (15 mg/kg) in combination with bitter gourd (300 mg/kg) showed synergistic hypoglycemic properties when compared to those that were fed with metformin or bitter ground alone [ 43 ]. However, the use of herbal medicine and higher doses of metformin was not found to be associated with good glycemic control in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Following the administration of alloxan, the animals’ blood glucose levels were checked using a glucometer. According to the protocols, in the in vivo study, mice with elevated blood sugar concentrations were also utilized [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study suggested that combination of both as treatment for diabetes mellitus was more effective than mono-therapy. 19,23 In type 2 diabetic patient, bitter gourd showed there is no difference for HbA1c levels from baseline and after 12 weeks treated by bitter gour standardized extract, while in placebo group, HbA1c levels showed significantly increased after 12 weeks of treatment compared to baseline. 24 Bitter gourd fruit juice could also reduce the enhanced fasting plasma glucose in patients with prediabetes.…”
Section: Momordica Charantiamentioning
confidence: 96%